Increasing the Number of Seats in the Island Council of the Public Entity of Bonaire: An Analysis if an Increasement of the Number of Seats in the Island Council Will Affect Good Governance Through Cumulation of Political Fragmentation - Cecilia, Willem A. (Archives of Business Research, 2022)
In 2019 an advisory group recommended an increase in the number of seats of the island councils of the Dutch Public Entities in the Caribbean. The discussion is if one should fully jump from nine to nineteen seats after the elections of 2027 regarding the public entity of Bonaire or should this be built gradually from nine to thirteen, fifteen, seventeen and nineteen after every election cycle. A higher number of council member seats can drive political instability and fragmentation which is widely considered to be a major obstacle to economic development. The quality of governance has significant impact on economic growth. In this paper the Gross Domestic Product (GDP) per capita is utilized to determine economic growth in relationship to the size of respectively a parliament, assembly and a council, to answer the research question if the size of the island council of the public entity of Bonaire, should be increased from nine to nineteen in 2027, or if this should be done in an incremental way to avoid cumulation of political fragmentation. Quantitative research involving analysis of several variables using accumulated data of the sizes of the parliaments, councils, and assemblies from different countries as the dependent variables, and the accumulated GDP per capita as the independent variable, will be conducted to test the nature of relationship between the dependent variable and the independent variables true multiple regression, to answer the research question.